PELATIHAN PERCAKAPAN BAHASA INGGRIS DALAM HOSPITALITI - Sandra Maleachi; Diena Mutiara Lemy; Kezia Christine; Verena Kimberly; Theresia Alexandra (Jurnal Sinergitas PKM & CSR, 2022)
English as an international language is very important in facilitating communication, especially in this era of globalization. It is important for those who work in the hospitality world and dealing with guests to have the ability to speak English. Having a workforce with the ability to speak English is very much needed because there are more and more foreign tourists in Indonesia. The ability to speak English is required by hotel employees so that they can communicate and provide good hospitality services and can be more easily understood by foreign guests. The basic level hospitality English conversation training for Emmanuel Foundation students aims to provide training to students at the Emmanuel Foundation so that they can have a broader knowledge in English, as well as how to speak English in the hospitality sector. The implementation is carried out online through the Google Meet platform as a support for activities that can be easily accessed by everyone. There is a preparation stage and an implementation stage (online training). This activity went well and systematically according to the arrangement of events that had been made. The pre-test and post-test sessions have the same questions. The pre-test was used to see the Emmanuel Foundation students' understanding of the material for simple English statements. The post-test was used to see whether or not there was an increase in the understanding of the Emmanuel Foundation students after the material was presented. Based on the results of the pre-test and post-test, it was shown that there was an increase in students' understanding from before and after the presentation of the material, although the results were not significant. Therefore, in the future this kind of training can be done even better.Keywords: English, conversation, hospitalityAbtract in bahasaBahasa Inggris sebagai bahasa internasional sangatlah penting dalam mempermudah komunikasi khususnya di era globalisasi ini.  Penting bagi mereka yang bekerja di dunia hospitaliti dan berhubungan langsung dengan tamu untuk memiliki kemampuan berbahasa Inggris. Memiliki tenaga kerja dengan kemampuan berbahasa Inggris sangat dibutuhkan karena turis asing semakin banyak di Indonesia. Kemampuan berbahasa Inggris diwajibkan oleh para karyawan hotel agar mereka dapat berkomunikasi dan memberikan pelayanan keramahtamahan yang baik dan dapat lebih mudah dimengerti oleh para tamu asing. Pelatihan percakapan bahasa inggris hospitaliti tingkat dasar bagi siswa/i Yayasan Emmanuel bertujuan  untuk memberikan pelatihan kepada siswa-siswi di Yayasan Emmanuel agar dapat memiliki pengetahuan yang lebih luas dalam Bahasa Inggris, serta cara berbicara dalam Bahasa Inggris di bidang hospitaliti. Pelaksanaan dilakukan secara daring melalui platfrom google meet sebagai penunjang kegiatan yang bisa diakses dengan mudah oleh setiap orang. Terdapat tahap persiapan dan tahap pelaksanaan (pelatihan daring). Kegiatan ini  berjalan dengan baik dan sistematis sesuai dengan susunan acara yang sudah dibuat. Sesi pre-test dan post-test memiliki pertanyaan yang sama. Pre-test digunakan untuk melihat pemahaman siswa/i Yayasan Emmanuel mengenai materi pernyataan bahasa Inggris sederhana. Post-test digunakan untuk melihat ada atau tidaknya peningkatan pemahaman siswa/i Yayasan Emmanuel setelah materi dipaparkan. Berdasarkan hasil pre-test dan post-test menunjukkan terdapat peningkatan pemahaman siswa/i dari sebelum dan sesudah pemaparan materi meskipun hasilnya tidak signifikan. Oleh karena itu, di masa yang akan datang pelatihan seperti ini bisa dilakukan lebih baik lagi.Kata Kunci: Bahasa Inggris, percakapan, hospitaliti